2014
DOI: 10.4187/respcare.02733
|View full text |Cite
|
Sign up to set email alerts
|

Head-of-Bed Elevation Improves End-Expiratory Lung Volumes in Mechanically Ventilated Subjects: A Prospective Observational Study

Abstract: BACKGROUND: Head-of-bed elevation (HOBE) has been shown to assist in reducing respiratory complications associated with mechanical ventilation; however, there is minimal research describing changes in end-expiratory lung volume. This study aims to investigate changes in end-expiratory lung volume in a supine position and 2 levels of HOBE. METHODS: Twenty postoperative cardiac surgery subjects were examined using electrical impedance tomography. End-expiratory lung impedance (EELI) was recorded as a surrogate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 32 publications
2
33
0
1
Order By: Relevance
“…25 EIT has been used to evaluate whether global and regional end-expiratory lung volumes improve by the degree of elevation. Spooner et al 26 found that head-of-bed elevation increases end-expiratory lung volumes and recommended, unless contraindicated, all mechanically ventilated patients should have their head of bed elevated. Figure 4 demonstrates the improvements in impedance by regions and the degree of elevation.…”
Section: Effects Of Position Changesmentioning
confidence: 99%
“…25 EIT has been used to evaluate whether global and regional end-expiratory lung volumes improve by the degree of elevation. Spooner et al 26 found that head-of-bed elevation increases end-expiratory lung volumes and recommended, unless contraindicated, all mechanically ventilated patients should have their head of bed elevated. Figure 4 demonstrates the improvements in impedance by regions and the degree of elevation.…”
Section: Effects Of Position Changesmentioning
confidence: 99%
“…A limitation of time-differencing EIT is that it is unable to detect the pre-existing EELI [ 18 , 19 ], which means it can only detect changes in EELI if the device remains in situ and running between readings [ 15 , 18 20 ]. Researchers, however, have successfully used EIT to detect changes in EELI due to various clinical interventions such as suctioning, position change, and changes in PEEP [ 13 , 16 , 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…As patient position has been shown to have an impact on ventilation distribution [101], we ensured that there were no significant changes in patient positioning throughout the data collection. A neonatal feeding catheter was inserted as described above and the pulse oximeter was positioned on the finger.…”
Section: Methodsmentioning
confidence: 99%
“…As transporting patients to radiology for CT is expensive and comes with increased risk [44,45], this was not an option. EIT, being a relatively new real-time radiation free bedside imaging tool [99][100][101][102], was found to be ideal in answering this key clinical question of whether patients' lungs are compromised when using SVs.…”
Section: Rationale and Significancementioning
confidence: 99%
See 1 more Smart Citation